Functional brain imaging with BOSS FMRI. - Miller, K; Hargreaves, B; Lee, J; Ress, D; deCharms, R; Pauly, J (2004)
The standard method for FMRI, using the blood oxygenation level dependent (BOLD) effect, has significant limitations that result from the coupling of functional contrast to sources of image artifact. We have developed an alternative method for FMRI based on balanced-SSFP imaging. This method uses the balanced-SSFP phase profile to invert the signal in deoxygenated blood relative to oxygenated blood. The resulting blood oxygenation sensitive steady-state (BOSS) signal decouples functional contrast from imaging, enabling significantly better image quality than BOLD FMRI. BOSS FMRI is very SNR-efficient, achieves strong functional contrast and is relatively immune to susceptibility gradients. In this paper, we present results validating the ability to detect functional activity using BOSS FMRI. One of the potential advantages of BOSS FMRI is the ability to acquire high-resolution data due to the SNR efficiency of balanced-SSFP. Preliminary high resolution results (1 x 1 x 2 mm/sup 3/) at 1.5 T are presented.